Standardised Sonneratia apetala Buch.-Ham. fruit extract inhibits human neutrophil elastase and attenuates elastase-induced lung injury in mice - Sengupta, Sayantan; Abhinav, Nipun; Singh, Sabita; Dutta, Joytri; Mabalirajan, Ulaganathan; Kaliyamurthy, Karthigeyan; Mukherjee, Pulok Kumar; Jaisankar, Parasuraman; Bandyopadhyay, Arun (Frontiers in Pharmacology, 2022)
Chronic obstructive pulmonary disease (COPD) along with asthma are major and increasing global health problems. Smoking contributes to about 80-90% cases of total COPD cases in the world. COPD leads to narrowing of small airways and destruction of lung tissue leading to emphysema primarily caused by neutrophil elastase. Neutrophil elastase plays an important role in disease progression in COPD patients and has emerged as an important target for drug discovery. Sonneratia apetala Buch.-Ham. is a mangrove plant widely found in the Sundarban regions of India. While the fruits of this plant have antibacterial, antifungal, antioxidant and astringent activities, fruit and leaf extracts have been shown to reduce the symptoms of asthma and cough. The aim of this study is to find whether fruit extracts of Sonneretia apetala inhibit neutrophil elastase and thus prevent the progression of neutrophil elastase-driven lung emphysema. The hydroalcoholic extract (Ethanol: water/ 90:10) of the Sonneratia apetala Buch.-Ham. fresh fruits (SAM) were used for neutrophil elastase enzyme kinetic assay and IC50 of the extract was determined. The novel HPLC method has been developed and the extract was standardized with Gallic acid and Ellagic acid as standards. The extract was further subjected to LC-MS2 profiling to identify key phytochemicals. The standardized S. apetala crude extract (SAM) contains 53µg/mg of Gallic acid and 95 µg/mg of Ellagic acid, based on the HPLC calibration. SAM also reversed the elastase-induced morphological change of human epithelial cells in vitro and an MTT assay was conducted to assess the viability. Further, 10mg/kg SAM had reduced alveolar collapse induced by neutrophil elastase in the mice model. Thus, in this study, we reported for the first time that fruit extract of S. apetala (SAM) has the potential to inhibit human neutrophil elastase in vitro and in vivo.